Administration, Prosopography and Appointment Policies in the Roman Empire Proceedings of the First Workshop of the International Network Impact of Empire (Roman Empire, 27 B.C. - A.D. 406), Leiden, June 28-July 1, 2000 - de Blois, L. (Impact of Empire, 2001)
Readership: All those interested in Roman history (also at the local level in communities in the Roman Empire), the history of ancient Greek and Roman religions, the representation of power of Roman emperors, and the connections between centre and periphery within the Roman Empire.